Yersinia enterocolitica: recovery and characterization of two unusual isolates from a case of acute enteritis. - Bottone, E J (1977)
Enteritis caused by Yersinia enterocolitica appears to be an uncommon occurrence in the United States. Most of the reported cases have been caused by biochemically typical Y. enterocolitica serotype O:8, the most frequently encountered serotype in the United States. The present report describes the isolation of two biochemically and serologically unusual Y. enterocolitica isolates from a patient with acute enteritis. One strain was distinguished by the rapid fermentation of rhamnose and raffinose and by citrate utilization at 22 degrees C but not at 37 degrees C. The other isolate was sucrose negative, and at either temperature it lacked both the fermentative capability for rhamnose and raffinose and the ability to utilize sodium citrate. Neither strain was agglutinable with known Y. enterocolitica antisera. The rhamnose-positive isolate showed an increased resistance to ampicillin, cephalothin, colymycin, and penicillin when tested at 22 degrees C as compared to results obtained at 37 degrees C. The demonstration that one patient's serum contained agglutinins (1:64) against the sucrose-negative strain supports its etiological significance. The role of the rhamnose-positive strain in the patient's illness is speculative. It conceivably could have potentiated the pathogenicity of the sucrose-negative isolate.